Overview of Monogenic or Mendelian Forms of Hypertension - Raina, Rupesh; Krishnappa, Vinod; Das, Abhijit; Amin, Harshesh; Radhakrishnan, Yeshwanter; Nair, Nikhil R.; Kusumi, Kirsten (Frontiers in Pediatrics, 2019)
Monogenic or Mendelian forms of hypertension are described as a group of conditions characterized by insults to the normal regulation of blood pressure by the kidney and adrenal gland. These alterations stem from single mutations that lead to maladaptive overabsorption of electrolytes with fluid shift into the vasculature, and consequent hypertension. Knowledge of these various conditions is essential in diagnosing pediatric or early-onset adult hypertension as they directly affect treatment strategies. Precise diagnosis with specific treatment regimens aimed at the underlying physiologic derangement can restore normotension and prevent the severe sequelae of chronic hypertension.